Feasibility study of heavy ion beam probe in CFQS quasi-axisymmetric stellarator. (1st June 2022) - Shimizu, A.; Isobe, M.; Okamura, S.; Kinoshita, S.; Ogawa, K.; Takahashi, H.; Oishi, T.; Yoshimura, Y.; Murase, T.; Nakagawa, S.; Tanoue, H.; Takubo, H.; et al.
Abstract: The world's first quasi-axisymmetric stellarator, CFQS, is now under construction. The CFQS will be dedicated to studies on the interaction between flow and turbulence, and confinement improvement by suppression of turbulence in connection with proof-of-principle experiment of quasi-axisymmetry. In order to conduct this experimental research, a heavy ion beam probe (HIBP) system is planned to be installed and utilized to measure the radial electric field and its fluctuation in a CFQS plasma. In this paper, an orbit calculation for a probe beam is performed to verify feasibility of the HIBP in the CFQS. The required beam energy, possible ion species, and the observable region in a CFQS plasma are investigated. The beam attenuation by a CFQS plasma is also estimated for different beam ion species. If we use 133 Cs + as a primary probe beam, the required beam energy is expected to be 30∼50 keV, which is relatively easy to handle. In this case the beam attenuation, evaluated by the ratio between the injected and detected beam currents, is 10 −3 ∼10 −2 in a CFQS plasma with a line-averaged electron density of <1.0 × 10 19 m −3 . For a higher density plasma, usage of 85 Rb + is better in terms of low-beam-attenuation, and a high signal-to-noise ratio. The HIBP in the CFQS will provide a great opportunity to study physics experimentally, related to the radial electric field, poloidal flow, and turbulence suppression.